PENGEMBANGAN E-MODUL COMMON RAIL UNTUK MENINGKATKAN HASIL BELAJAR PADA KOMPETENSI PERAWATAN BAHAN BAKAR MESIN DIESEL DI SMK NEGERI JAWA TENGAH - Zaka, Ahmad Murtadlo; Supraptono, Supraptono (Automotive Science and Education Journal, 2020)
The purpose of this study is to develop an electronic module of common rail systems to contribute to learning outcomes, find out the feasibility, and effectiveness of students towards the use of common rail e-modules developed. The e-module development model uses ADDIE development. Based on the results of the product feasibility test, the final data percentage is 80.00% for media experts and 85.63% for material experts, so that the common rail e-module products meet the feasible and very feasible categories. E-modules contribute to student learning outcomes seen from the difference in the average value of the pretest-posttest by 16.06. The t-test shows the value of tcount= 8.91> ttable= 2.080. The contribution of student learning outcomes is obtained by the average N-Gain test of 0.5622 with the criteria for the contribution of student learning outcomes to being. Analysis of student effectiveness obtained a percentage of 91.86% included in the excellent category